2018
DOI: 10.4236/ojneph.2018.81003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Renal Biomarkers of Renal Function in Commercial Automobile Workers in Benin City, Edo State, Nigeria

Abstract: Background: Blood-urea nitrogen, creatinine, uric acid and electrolytes are important biomarkers of renal function which could be considered as suitable prognostic indicators of renal dysfunction. Aim: The aim of this work was to assess renal biomarkers of renal function in commercial automobile workers in Benin City, Edo State, Nigeria. Methodology: A total of 158 males within the ages of 18-60 years participated in this study, 50 of which are control subjects. They were recruited for this study from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…The prevalence of hyperuricemia was significantly higher in the automobile mechanics compared to the control. This finding is keeping with report of previous studies conducted within and outside Nigeria [ 9 , 32 , 47 , 48 ]. Hyperuricemia is a non-traditional cardiovascular risk factor that is associated with target organ damage, cardiovascular morbidity and mortality [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of hyperuricemia was significantly higher in the automobile mechanics compared to the control. This finding is keeping with report of previous studies conducted within and outside Nigeria [ 9 , 32 , 47 , 48 ]. Hyperuricemia is a non-traditional cardiovascular risk factor that is associated with target organ damage, cardiovascular morbidity and mortality [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was observed that 50-nm SiNPs after its distribution throughout the kidney can be eliminated through kidney by urine [19] . To evaluate renal damage, parameters such as levels of urea, creatinine and electrolyte (e.g., Na+ and K+) are used [4] . In the present study, significant increases in the serum urea and creatinine have been observed, while no significant differences were found in Na+ , and K+ content in SiNPs treated and control group.…”
Section: Discussionmentioning
confidence: 99%
“…One of the initially observed hematological effects of lead poisoning is the basophilic stippling's of erythrocytes which is potential biomarker for detection of lead toxicity. This aggregates as products of degradation of ribonucleic acid [33]. Lead directly affects the hematopoietic system through restraining the synthesis of hemoglobin by inhibiting various key enzymes involved in the heme synthesis pathway.…”
Section: Hematological Indices As Biomarkers Of Lead Exposurementioning
confidence: 99%